Antibiotic prophylaxis - Vasconcelos, Carlos (2010)
Antibiotic prophylaxis takes the prevention of the infection as an objective, through the administration of antimicrobians. There are benefits and potential damages in this medical attitude obligating to a cost - benefits analysis, which must take into account factors as the gravity of the disease to prevent, activity of the microbial agent, induction of resistances, toxicity, etc. This text is about antibiotic prophylaxis in endocarditis and in surgery procedures reporting the experience of the Hospital Santo António (HSA). The international recommendations for antibiotics administration in endocarditis made it more selective, taking into account that the bacteriemia resultant of the daily activities has bigger probability of causing infectious endocarditis than the bacteriemia associated to odontologic proceedings and that, only a scarce number of cases might be prevented even that the antibiotic prophylaxis is 100 % effective. Surgical site infection (SSI) it is an important problem, occupying in the HSA the third place of the nosocomial infections (NI), after UTI and respiratory infections. In a series of 15000 surgical procedures the rate of NI was 3,36 %, with a highly probable subnotification. The most frequent type of SSI is superficial incision and the commonest microbial agents were the methicilin-resistant Staphylococus aureus and the Escherichia coli. Appendicectomy and the wound desbridment / abscesses were the surgical procedures that more contributed to SSI. The strategy followed, in 1995, by the HSA for antibiotic prophylaxis in surgery was based on the Recommendations of “Surgical Wound Task Force Guidelines for the prevention of Surgical Wound Infection” and of “Center for Disease Control”, in an initiative of the group of antimicrobial - committee of pharmacy and therapeutics, with the support of the Administration and the involvement of several specialists. In a global evaluation of the adhesion to the published recommendations we note that the correct use exceeded 60% in clean surgery without use of prothesis. Of the remainder, nearly 30 % did not do prophylactic antibiotic and only 6 % did it wrongly as therapeutic intention. This last percentage increases for the double in the clean-contaminated, contaminated and dirty, as well as in the emergency surgery. The experience of the HSA allows us to affirm that the fulfillment of a protocol of antibiotic prophylaxis in surgery can be got with the involvement from the beginning, in the process, of the responsible persons and with efficient measures of control and of easy application.